2‐Difluoromethoxy‐Substituted Estratriene Sulfamates: Synthesis, Antiproliferative SAR, Antitubulin Activity, and Steroid Sulfatase Inhibition. (13th October 2022) - Dohle, Wolfgang; Asiki, Hannah; Gruchot, Wojciech; Foster, Paul A.; Sahota, Havreen K.; Bai, Ruoli; Christensen, Kirsten E.; Hamel, Ernest; Potter, Barry V. L.
Abstract: 2‐Difluoromethoxyestratriene derivatives were designed to improve potency and in vivo stability of the drug candidate 2‐methoxyestradiol (2ME2). Compound evaluation i n vitro against the proliferation of MCF‐7 and MDA MB‐231 breast cancer cells, as inhibitors of tubulin polymerisation and also steroid sulfatase (STS) both in cell lysates and in whole cells, showed promising activities. In antiproliferative assays 2‐difluoromethoxyestradiol was less potent than 2ME2, but its sulfamates were often more potent than their corresponding non‐fluorinated analogues. The fluorinated bis‐sulfamate is a promising antiproliferative agent in MCF‐7 cells (GI50 0.28 μM) vs the known 2‐methoxyestradiol‐3, 17‐ O, O ‐bissulfamate (STX140, GI50 0.52 μM), confirming the utility of our approach. Compounds were also evaluated in the NCI 60‐cell line panel and the fluorinated bis‐sulfamate derivative displayed very good overall activities with a sub‐micromolar average GI50 . It was a very potent STS inhibitor in whole JEG‐3 cells (IC50 3.7 nM) similar to STX140 (4.2 nM) and additionally interferes with tubulin assembly in vitro and colchicine binding to tubulin. An X‐ray study of 2‐difluoromethoxy‐3‐benzyloxyestra‐1, 3, 5(10)‐trien‐17‐one examined conformational aspects of the fluorinated substituent. The known related derivative 2‐difluoromethyl‐3‐sulfamoyloxyestrone was evaluated for STS inhibition in whole JEG‐3 cells and showed an excellent IC50 of 55 pM. Abstract : Difluoromethoxyestradiene‐based steroid sulfatase (STS) inhibitors have been designed. Six difluoromethoxy‐substituted steroid dervatives were synthesised and evaluated in vitro against the proliferation of MCF‐7 and MDA MB‐231 breast cancer cells. Bis‐sulfamate 10 was identified as a promising antiproliferative agent (GI50 0.28 μM in MCF‐7 cells), a potent STS inhibitor (IC50 3.7 nM in JEG‐3 cells) and an inhibitor of tubulin assembly in vitro and colchicine binding to tubulin.